2019
DOI: 10.1200/po.18.00413
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Neuroblastoma Cells Are Undetected by Current mRNA Marker Panels: The Development of a Specific Neuroblastoma Mesenchymal Minimal Residual Disease Panel

Abstract: PURPOSE Patients with neuroblastoma in molecular remission remain at considerable risk for disease recurrence. Studies have found that neuroblastoma tissue contains adrenergic (ADRN) and mesenchymal (MES) cells; the latter express low levels of commonly used markers for minimal residual disease (MRD). We identified MES-specific MRD markers and studied the dynamics of these markers during treatment. PATIENTS AND METHODS Microarray data were used to identify genes differentially expressed between ADRN and MES ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…The number of control samples with expression of our markers was slightly increased, possibly due to the more efficient cDNA synthesis. However, ΔCt results were comparable to earlier established thresholds ( Table S3 ), with the exception of FMO3 in BM, which showed an expression of 2.2 Ct lower than previously published data [ 9 , 13 ]. Of note, FMO3 amplifications were not detected in unconverted RNA, excluding the possibility that detection of gDNA resulted in lower Ct values.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The number of control samples with expression of our markers was slightly increased, possibly due to the more efficient cDNA synthesis. However, ΔCt results were comparable to earlier established thresholds ( Table S3 ), with the exception of FMO3 in BM, which showed an expression of 2.2 Ct lower than previously published data [ 9 , 13 ]. Of note, FMO3 amplifications were not detected in unconverted RNA, excluding the possibility that detection of gDNA resulted in lower Ct values.…”
Section: Resultssupporting
confidence: 88%
“…In the current protocols, BM infiltration at diagnosis and during treatment is assessed by histology or (immuno)cytology, and more sensitive detection of tumor cells by reverse-transcriptase quantitative polymerase chain reaction (RT-qPCR) is under investigation [ 8 , 9 , 10 ]. Multiple studies showed that detection of MRD with various mRNA markers throughout and post-induction therapy could be prognostic of outcome [ 3 , 4 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, ADRN-type cells represent a more differentiated state, with similarities to the ADRN lineage as in chromaffin cells (van Groningen et al, 2017). ADRN mRNAs decrease during the treatment of NB patients, which may indicate the depletion of ADRN cells in the tumor (Wezel et al, 2019). An ADRN gene enrichment was observed for genes responding to DLG2 Article ll OPEN ACCESS overexpression (2.6 times enriched, p = 4.3eÀ5, Fisher's exact test), but not for genes responding to RA treatment (p = 0.46; Figure 3D).…”
Section: Dlg2 Overexpression Potentiates Ngf-induced Nb Cell Differenmentioning
confidence: 97%